Application of continuous glucose monitoring system in blood glucose monitoring for patients with type 2 diabetes mellitus (动态血糖监测系统在2型糖尿病患者血糖监测中的应用) - WANG LI (王丽); WANG Shun (王舜) (中西医结合护理)
Objective To explore the application value of continuous glucose monitoring system(CGMS) in blood glucose monitoring for patients with type 2 diabetes mellitus(T2DM). Methods Totally 110 patients with type 2 diabetes mellitus were enrolled as research objects. The CGMS was used in the in blood glucose monitoring, while the blood glucose test using finger-prick blood was conducted as a reference. The application value of CGMS was evaluated and outcome of hypoglycemic events was recorded. Results The Largest Amplitude of Glycemic Excursions(LAGE) was (8. 50±2. 88) mmol/L, and the Absolute Means of Daily Difference(MODD) (0. 94±0. 35) mmol/L. Totally 33 patients with 95 times of hypoglycemic events were observed by CGMS, while only 11 patients with 18 times of hypoglycemic events were observed by blood glucose test using finger-prick blood. Conclusion Combined with finger-prick blood glucose test as a reference, CGMS can provide guidance for clinical treatment, dietary guidance and lifestyle for T2DM patients. (目的 探讨动态血糖监测系统(CGMS)在2型糖尿病患者血糖监测中的应用价值。方法 选取110例2型糖尿病患者为研究对象, 采用CGMS进行血糖监测, 同时应用指尖血糖仪监测血糖。评估CGMS应用效果, 比较2种监测方法下低血糖事件发生情况。结果 患者血糖最大波动幅度(LAGE)(8. 50±2. 88)mmol/L、日间血糖平均绝对差(MODD) (0. 94±0. 35) mmol/L。CGMS监测到33例患者发生95例次低血糖, 指尖血糖仪仅监测到11例18例次低血糖。结论 住院2型糖尿病患者应用CGMS进行监测, 结合指尖血糖监测作为参照比较, 可以为临床治疗、饮食指导和生活方式提供指导。)